2021
DOI: 10.1371/journal.pone.0257988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of political versus expert messaging on vaccination intentions of Trump voters

Abstract: To increase COVID-19 vaccine uptake in resistant populations, such as Republicans, focus groups suggest that it is best to de-politicize the issue by sharing five facts from a public health expert. Yet polls suggest that Trump voters trust former President Donald Trump for medical advice more than they trust experts. We conducted an online, randomized, national experiment among 387 non-vaccinated Trump voters, using two brief audiovisual artifacts from Spring 2021, either facts delivered by an expert versus po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…In addition, support for and attention to Donald Trump's 2020 candidacy are strongly linked to beliefs in conspiracy theories since the former President was a significant spreader of misinformation (Choi 2021; Mazzei and Medina 2020; Uscinski 2020). Trump supporters relied on the President for information, including medical advice (Robertson, 2021). This is consistent with findings that Republicans are more likely to believe in conspiracy theories because Republican elites have been claiming the media are bias and potentially corrupt (Uscinski et al 2016).…”
Section: Hypothesessupporting
confidence: 77%
“…In addition, support for and attention to Donald Trump's 2020 candidacy are strongly linked to beliefs in conspiracy theories since the former President was a significant spreader of misinformation (Choi 2021; Mazzei and Medina 2020; Uscinski 2020). Trump supporters relied on the President for information, including medical advice (Robertson, 2021). This is consistent with findings that Republicans are more likely to believe in conspiracy theories because Republican elites have been claiming the media are bias and potentially corrupt (Uscinski et al 2016).…”
Section: Hypothesessupporting
confidence: 77%
“…Similar to findings by Liu et al that found a positive correlation between seeking COVID-19-related information on digital media and practising preventive behaviours [42] , our study found seeking information from digital sources and non-health related governmental agencies and family, friends and influencers to be positively associated with high vaccine intent. A USA based study suggested that vaccination uptake can be increased if one identifies with the political speaker who is endorsing it and they also found that a factually accurate message by an expert may not be effectual to increase vaccination uptake [43] . Bonnevie et al found influencers to significantly increase beliefs on flu vaccine and they have been engaged to not only market products but also to promote vaccination [44] .…”
Section: Discussionmentioning
confidence: 99%
“…While in the first months of the pandemic, a vaccination was a desired yet distant prospect, and a discussion around vaccinating specific population groups before others evolved [ 9 ], the tide has now turned in many first-world countries: The vaccine is actively rejected by certain groups, and demonstrations against anti-COVID-19 measures are happening. Partly being organized with the hidden agenda of disseminating extremist ideas [ 12 ], this development often stems from a mistrust towards established political systems – rooted in minority and socioeconomically disadvantaged communities, and fueled by social media campaigns and fake news [ 10 , [13] , [14] , [15] ]. Countermeasures as involving scientific experts in the ongoing discussion are only sometimes productive [ 14 , 16 ], and even highly educated population groups may be in need of additional information around vaccinations to increase an informed decision making [ 13 ].…”
Section: From Shortage To Rejectionmentioning
confidence: 99%
“…Partly being organized with the hidden agenda of disseminating extremist ideas [ 12 ], this development often stems from a mistrust towards established political systems – rooted in minority and socioeconomically disadvantaged communities, and fueled by social media campaigns and fake news [ 10 , [13] , [14] , [15] ]. Countermeasures as involving scientific experts in the ongoing discussion are only sometimes productive [ 14 , 16 ], and even highly educated population groups may be in need of additional information around vaccinations to increase an informed decision making [ 13 ]. For already-stretched healthcare personnel, the violation of the moral principle not to inflict harm upon others through their own actions [ 17 ] is hard to take – for instance, if you can directly see a demonstration outside through the hospital window when you are about to intubate a critically-ill COVID-19 patient [ 11 ].…”
Section: From Shortage To Rejectionmentioning
confidence: 99%
See 1 more Smart Citation